Ultra high vacuum cathodic arc for deposition of superconducting lead photo-cathodes - Strzyzewski, P.; Langner, J.; Sadowski, M.J.; Witkowski, J.; Sekutowicz, J. (Вопросы атомной науки и техники, 2007)
The paper presents recent experimental studies aimed at the deposition of superconducting films of pure lead (Pb) by means of the UHV cathodic arc. Such layers can be used as photo-cathodes needed for modern accelerator injectors. The system configuration, used for thin film deposition inside the RF Gun designed at DESY is also described. The paper presents also the main results of Pb-films measurements, which were performed by means of SEM and SIMS techniques. Представлено результати недавніх експериментальних досліджень, що мають метою осадження надпровідних чисто свинцевих (Pb) плівок за допомогою ультра-высоковакуумної катодної дуги. Такі шари можуть бути використані як фотокатоди для сучасних інжекторів у прискорювачах. Описано конфігурацію системи, яка використана для осадження плівок усередині ВЧ-інжектора, розробленого в DESY. Також представлені основні результати вимірів характеристик свинцевих плівок, виконаних за допомогою SEM and SIMS. Представлены результаты недавних экспериментальных исследований, имеющих целью осаждение сверхпроводящих чисто свинцовых (Pb) пленок с помощью ультра-высоковакуумной катодной дуги. Такие слои могут быть использованы в качестве фотокатодов для современных инжекторов в ускорителях. Описана конфигурация системы, использованная для осаждения пленок внутри ВЧ-инжектора, разработанного в DESY. Также представлены основные результаты измерений характеристик свинцовых пленок, выполненных с помощью SEM and SIMS.